Effectiveness of the combined use of fitness training and changes in the diet depending on the initial body weight - Elikov, A.V.; Tsapok, P.I.; Karpova, E.M.; Loktev, D.B. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of the combined use of fitness training and dietary changes depending on the initial body mass index. Methods and structure of the study. 81 untrained women aged 48.9±2.4 years were examined. Depending on the initial body mass index, women were divided into four groups. Fitness training was carried out using body weight and without the use of sports equipment, lasting 45 minutes, three times a week, in groups of 6-8 people. Results and conclusions. In all groups, a decrease in the body mass index and circumference of the studied parameters was established, but the degree of change in individual anthropometric parameters depended on the initial body weight. At normal body weight, only a statistically significant downward trend in waist circumference was found; with overweight, a significant decrease was found in the circumference of the hips and arms; with obesity, a significant decrease was found in the circumferences of the chest, waist and hips, more pronounced in women with obesity of the 1st degree. The use of a complex of fitness training with a change in diet helps to reduce the circumference of the chest, waist, hips, legs, arms, and body mass index.